Evaluation of the Science Laboratory Applications Course in a Pre-service Primary School Teacher Curriculum - Nebi Altunova; Hüseyin Artun (Universitas Pendidikan Indonesia, 2020)
In this study, the Science Laboratory Applications (SLA) course given in a department of Elementary School Teaching in Turkey was evaluated for effectiveness. A triangulation research design, with mixed methods, was employed based on research data collected via a semi-structured interview form, a Science Experiments Evaluation Rubric (SEER) developed by the researchers, and the researchers’ diary notes. The study group included 66 preservice teachers in their second year of study. To select the participants, a maximum variation sampling method was used with the qualitative interviews. The SEER scores were analyzed using the packaged software of SPSS, while interview data were evaluated using content analysis, and descriptive analysis was applied to the researcher’s diary notes. The quantitative and qualitative results obtained in the study revealed that preservice teachers achieved the course outcomes as well as the objectives of the curriculum. Based on these results, several suggestions are put forward for future researchers and practitioners.Keywords Elementary school preservice teacher, curriculum evaluation, course of science laboratory applications